Relações bioquímicas e moleculares da germinação e emergência em arroz vermelho, inoculado com Herbaspirillum seropedicae - Bonfim, Cristiano Oliveira (2022)
The study investigated the potential of the bacterium Herbaspirillum seropedicae (Hs) in optimizing the germination and initial growth of red rice (Oryza sativa L.). The research employed six different treatments, including seeds soaked in water, gibberellic acid, and inoculated with H. seropedicae. Results revealed that the treatment with non-soaked seeds inoculated with H. seropedicae significantly increased various variables such as germination, germination speed index, root length, total fresh mass, among others, compared to non-soaked and non-inoculated seeds. Statistical analysis confirmed the significance of the treatment effects, highlighting the positive influence of the bacterium on physiological, and biochemical variables. The concentration of gibberellic acid solution (GA3) also played a crucial role in the observed outcomes. The findings point to the agronomic and biotechnological potential of H. seropedicae in promoting red rice growth, regardless of seed soaking. These results suggest that inoculation with H. seropedicae could be an effective strategy to enhance the germination and early development of this crop, providing valuable insights for more sustainable and efficient agricultural practices.